COMMUNITY-BASED ENTREPRENEURSHIP: A COMMUNITY DEVELOPMENT MODEL TO BOOST ENTREPRENEURIAL COMMITMENT IN RURAL MICRO ENTERPRISES - Ambara Purusottama; Teddy Trilaksono; Agus W. Soehadi (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. Micro enterprises (MEs) have been proven to be significant contributors to the national economy, particularly for marginal communities. However, only a few programs are aimed to encourage ME improvement, especially in rural areas. The community-based entrepreneurship (CBE) program led by higher education institutions has been recognized as an effective instrument to accelerate capacity building for marginal communities. This research aims to determine the effectiveness of this program in boosting entrepreneurial commitment of rural MEs to help them develop their business. Applying the theory of planned behavior (TPB) framework, this research applies a direct survey to respondents from rural MEs. Then to analyze both data and output, this study applies PLS-SEM tool with SmartPLS software. Results reveal that social factors (social pressure and environmental influence) do not incline rural ME entrepreneurs to develop their business. Attitude factors (entrepreneurial benefit and willingness to take a risk) become the most dominant variables, and consistently have an impact on rural ME entrepreneurs in developing their business. To implement the business development of rural ME, perceived behavioral control becomes a main determinant. Demographic profiles (age, gender, and eduction) is also heavily as influential factors.